The monosaccharide transporter(-like) gene family in Arabidopsis - Büttner, Michael (FEBS letters, 2007)
The availability of complete plant genomes has greatly influenced the identification and analysis of phylogenetically related gene clusters. In Arabidopsis, this has revealed the existence of a monosaccharide transporter(-like) gene family with 53 members, which play a role in long-distance sugar partitioning or sub-cellular sugar distribution and catalyze the transport of hexoses, but also polyols and in one case also pentoses and tetroses. An update on the currently available information on these Arabidopsis monosaccharide transporters, on their sub-cellular localization and physiological function will be given.